Entre abismos: o caos e a entropia num percurso artístico - Viegas, Inês Marisa da Encarnação (2021)
This work project aims to develop a study based on the observation, contemplation and interpretation of destructive and catastrophic processes, in the resulting evolution of Entropy, and the Abyss, making it possible to capture singular moments and perspectives, which may represent, from the artistic point of view, Chaos. It’s also intended to look at the theme of Chaos, Entropy and Abyss from other perspectives, which may complement a strict approach from an artistic vision, framing it in a multifaceted, philosophical, moral, religious and, ultimately, scientific way. Examples of artists and their works, representing an aesthetic approach to the proposed theme, are included as examples of complementarity or even counterpoint, relative to the set of my own art works, developed over the past few years and related to the topics covered.